Platform ASA Anak Indonesia : Kolaborasi Masyarakat Sipil Merespon Lonjakan Jumlah Anak Yatim saat Covid-19 - Try Sujatmiko Ramadhani (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the role of civil society in responding to the surge in the number of orphans during the Covid-19 pandemic. Although child mortality during the pandemic tended to be low, children were affected by a “hidden pandemic” in which they became orphans due to the loss of parents or primary caregivers. The ASA Anak Indonesia platform is a civil society initiative established by Zakat Management Organizations (LAZ) under the coordination of the Zakat Forum (FOZ) to respond to this issue. This research employs a descriptive method with a qualitative approach. The findings are analyzed using social capital theory, which encompasses the processes of bonding, bridging, and linking. The results show that the program was able to realize these three processes through internal consolidation within each institution, coordination among LAZs, and collaboration with the government. This study also provides a basis for understanding that the social capital formed can become a latent asset for responding to strategic issues in the future. Furthermore, the data on orphans collected through this platform faces future challenges regarding how it can be synergized with relevant government agencies.